2015
DOI: 10.1016/j.elecom.2015.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Flexible graphite film with laser drilling pores as novel integrated anode free of metal current collector for sodium ion battery

Abstract: In this work, flexible polyimide graphite films with laser drilling pores were prepared by laser drilling pore technique. Then a full cell was built based on the porous graphite film anode, Na 3 V 2 (PO 4 ) 3 cathode, and NaPF 6 in diglyme electrolyte. This unique battery system makes the best of co-intercalation mechanism of Na + -solvent into porous graphite film host. Moreover, the porous graphite film is directly served as an integrated anode with no electrochemically inactive components, such as binders, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…However, the capacity retention was only 70% after 250 cycles at 0.5 A g −1 , which may be attributed to the high cutoff voltage of 4.2 V inducing decomposition of the ether‐based electrolyte during charging. Other graphitic‐carbon‐based full cells, such as graphite//Al 2 O 3 @Na 3 V 2 (PO 4 ) 3 , porous graphite//Na 3 V 2 (PO 4 ) 3 , carbon nanotube@carbon black//Na 3.12 Fe 2.44 (P 2 O 7 ) 2 , and multiwalled carbon nanotube @graphite oxide nanoribbon//Na x MnO 2 have also been reported. However, none of these full cells exhibited output voltages above 3 V and a cyclic life beyond 1000 cycles, indicating that great efforts are needed to develop advanced Na‐ion full cells.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…However, the capacity retention was only 70% after 250 cycles at 0.5 A g −1 , which may be attributed to the high cutoff voltage of 4.2 V inducing decomposition of the ether‐based electrolyte during charging. Other graphitic‐carbon‐based full cells, such as graphite//Al 2 O 3 @Na 3 V 2 (PO 4 ) 3 , porous graphite//Na 3 V 2 (PO 4 ) 3 , carbon nanotube@carbon black//Na 3.12 Fe 2.44 (P 2 O 7 ) 2 , and multiwalled carbon nanotube @graphite oxide nanoribbon//Na x MnO 2 have also been reported. However, none of these full cells exhibited output voltages above 3 V and a cyclic life beyond 1000 cycles, indicating that great efforts are needed to develop advanced Na‐ion full cells.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Flexible polyimide graphite films have a highly in‐plane ordered structure, which results in the enhanced electrical conductivity and excellent mechanical strength . A novel porous graphite film for an integrated anode through laser drilling technique has been reported . It displays moderate discharge capacity of 127 mAh g –1 with superior cycling stability for 1000 cycles.…”
Section: Non‐aqueous Anode‐based Sifcsmentioning
confidence: 99%
“…Moreover, the graphite anode provided superior cycle stability (more than 2500 repetitive electrochemical cycles), demonstrating the reversibility of the co‐intercalation chemistry despite the large volume expansion of ≈345% . Subsequent research conducted by Cui and co‐workers also demonstrated the practical feasibility of [sodium–ether] + complex ion intercalation in NIBs and sodium‐ion capacitors with good cycle stability …”
Section: Introductionmentioning
confidence: 99%